Multisystem Inflammatory Syndrome After Mild COVID-19 Infection in a Fully Vaccinated Adult - Zachary Banbury; Abdullah Ahmad; Enrique Baez; Danielle Pope; Natasha Rastogi; Fausto G. Lisung (Annals of Internal Medicine: Clinical Cases)
Multisystem inflammatory syndrome in adults (MIS-A) is a rare and severe complication of SARS-CoV-2 infection that is more common in children than adults. It is often underdiagnosed by physicians because of the heterogeneity of symptoms, overlapping comorbid conditions, and a lack of comprehensive work-up. Here, we present a patient case of MIS-A after mild COVID-19 infection in a fully vaccinated adult. The goal of this case is to describe the presentation of MIS-A in adults and review the associated laboratory results that can guide early diagnosis and management to improve outcomes.